Rotavirus Strains Bearing Genotype G9 or P[9] Recovered from Brazilian Children with Diarrhea from 1997 to 1999 - Santos, Norma (American Society for Microbiology, 2001)
Human rotavirus strains belonging to genotype G9 or P[9] were detected in a collection of stool specimens from children with diarrhea in two cities of the state of Rio de Janeiro, Brazil, between March 1997 and December 1999. G9 strains were first detected in April 1997 and remained prevalent until the end of the study, at a frequency of 15.9% (n = 157). A high percentage of VP7 nucleotide (99.0 to 99.5%) and deduced amino acid identity (98.6 to 99.1%) was found between three randomly selected Brazilian G9 strains and the American G9 strain US1205. A novel G9:P[4] genotype combination was detected in addition to G9:P[8] and G9:P[6], demonstrating that this G genotype may undergo constant genetic reassortment in nature. The P[9] rotavirus strains constituted 10.2%, the majority of which were detected between April and July 1997. The RNA electrophoretic migration pattern of the G3:P[9] strains resembled that of AU-1 virus (G3:P3[9]), suggesting a genetic similarity between the Brazilian G3:P[9] strains and the Japanese virus, which is similar to a feline rotavirus genetically.